2011
DOI: 10.1186/1752-1947-5-369
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary ischemia during alcohol withdrawal: a case report

Abstract: IntroductionThe potential of alcohol withdrawal to cause acute coronary events is an area that needs the urgent attention of clinicians and researchers.Case presentationWe report the case of a 52-year-old heavy-alcohol-using Sri Lankan man who developed electocardiogram changes suggestive of an acute coronary event during alcohol withdrawal. Despite the patient being asymptomatic, subsequent echocardiogram showed evidence of ischemic myocardial dysfunction. We review the literature on precipitation of myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…We wish to highlight the potential for acute alcohol withdrawal to cause sudden cardiac death by precipitating acute coronary events and fatal cardiac arrhythmias and present some cases in our hospital that relate to this. There are a few case reports published in this regard . In addition a prospective study of electrocardiographic (ECG) tracings of 19 patients in alcohol withdrawal showed that seven of them had horizontal or down sloping ‘suspicious’ ST segment depressions though none of them complained of clinical symptoms .…”
Section: Declarations Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…We wish to highlight the potential for acute alcohol withdrawal to cause sudden cardiac death by precipitating acute coronary events and fatal cardiac arrhythmias and present some cases in our hospital that relate to this. There are a few case reports published in this regard . In addition a prospective study of electrocardiographic (ECG) tracings of 19 patients in alcohol withdrawal showed that seven of them had horizontal or down sloping ‘suspicious’ ST segment depressions though none of them complained of clinical symptoms .…”
Section: Declarations Of Interestmentioning
confidence: 99%
“…There are several theories as to how withdrawal states may precipitate acute coronary events such as; stimulation of coronary vessels by a withdrawal‐induced adrenergic surge, imbalance of α and β adrenergic stimulation of coronaries , long term alcohol induced structural damage limiting coronary autoregulation at times of stress , magnesium deficiency and autonomic neuropathy .…”
Section: Declarations Of Interestmentioning
confidence: 99%
“…Cannabis remains one of the most universally abused recreational drugs worldwide and its popularity has increased considerably due to the recent legalization and medicinal use [1][2][3][4][5]. Sometimes, cannabis overuse can lead to malignant arrhythmia leading to cardiac arrest [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis remains one of the most universally abused recreational drugs worldwide and its popularity has increased considerably due to the recent legalization and medicinal use [1][2][3][4][5]. Sometimes, cannabis overuse can lead to malignant arrhythmia leading to cardiac arrest [5,6]. Alcohol withdrawal following binge drinking combined with cannabis abuse can lead to malignant arrhythmia, seizure, and at times culminating in cardiac arrest [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation